A "center-determination" phenomenon of C13H27CO-Gly-Ala-Ala lipotripetides: relationship between the molecular chirality and handedness of organic self-assemblies. (28th June 2019) - Guo, Kexiao; Zhang, Lianglin; Lin, Shuwei; Li, Yi; Li, Baozong; Yang, Yonggang
Abstract : The chirality of the central alanine residue dominates the handedness of molecular packing and that of organic self-assemblies. Abstract : A series of C13 H27 CO-Gly-Ala-Ala tripeptides with different chiralities are synthesized. They can form physical gels in toluene and 1, 4-dioxane. They self-assemble into right- or left-handed twisted nanoribbons in a mixture of methanol and water. It is found that the handedness of the nanoribbons is controlled by the chirality of the alanine residue at the center. Circular dichroism characterization also revealed that the peptide segment packing handedness was dominated by the chirality of the central alanine residue. The formation of self-assemblies was studied using 1 H NMR and particle size distribution. Upon decreasing the temperature, the micelle forms a fine aggregate and then grows into twisted nanoribbons. It was also found from 1 H NMR characterization that H-bonds formed by the central alanine residue played an important role in the formation of the self-assemblies. The X-ray diffraction patterns showed that the tripeptides packed into lamellar structures.